Environmental Health Risk Assessment of Hydrogen Sulfide and Ammonia Exposure among Scavengers at Jatibarang Landfill Semarang City - Lina Nur Qolifah; Suhartono Suhartono; Nurjazuli Nurjazuli (Jurnal Ilmiah Kesehatan (JIKA), 2026)
The City of Semarang generated the largest volume of waste in Central Java Province, with 72.01% deposited at the Jatibarang Landfill. The waste was predominantly domestic and had the potential to produce H₂S and NH₃ gases, which might pose health risks. This study aimed to assess the health risks associated with exposure to H₂S and NH₃ among waste pickers at the Jatibarang Landfill. An EHRA approach was applied, involving 77 waste pickers selected through simple random sampling from a total population of 250. Ambient air samples were collected at five locations within the landfill based on areas with the highest scavenging activity. The measured concentrations showed that average H₂S levels were 0.001 ppm and NH₃ levels averaged 0.0168 ppm. Mean exposure duration, frequency, length of employment, and body weight were 24 hours/day, 325.71 days/year, 11 years, and 57.05 kg, respectively. The average H₂S exposure intakes for real-time and realtime exposurewere 1.40 × 10⁻⁴ and 3.23 × 10⁻⁴ mg/kg/day, while NH₃ exposure intakes were 1.66 × 10⁻³ and 3.81 × 10⁻³ mg/kg/day. The cumulative risk characterization for real-time exposure indicated that 100% of waste pickers had RQcum ≤ 1, suggesting no immediate health risk. In contrast, the lifetime projection showed that 100% had RQcum > 1, indicating potential long-term health risks. These findings underscore the need for effective risk management strategies to mitigate health hazards from NH₃ and H₂S exposure among waste pickers at the Jatibarang Landfill in Semarang.